2016
DOI: 10.1088/0953-8984/28/31/315403
|View full text |Cite
|
Sign up to set email alerts
|

Calculated high-pressure structural properties, lattice dynamics and quasi particle band structures of perovskite fluorides KZnF3, CsCaF3and BaLiF3

Abstract: A detailed study of the high-pressure structural properties, lattice dynamics and band structures of perovskite structured fluorides KZnF 3 , CsCaF 3 and BaLiF 3 has been carried out by means of density functional theory. The calculated structural properties including elastic constants and equation of state agree well with available experimental information. The phonon dispersion curves are in good agreement with available experimental inelastic neutron scattering data. The electronic structures of these fluor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…The GGA band gap values were determined to be 3.36 eV for Zn 3 P 2 O 8 and 2.3 eV for Zn 3 V 2 O 8 , whereas the TB-mBJ band gap values were found to be 6.17 eV for Zn 3 P 2 O 8 and 3.18 eV for Zn 3 V 2 O 8 . It is worth noting that our calculations are in alignment with earlier theoretical reports on Zn 3 V 2 O 8 , [37,38] [39] where even the GW band gap was found overestimating the experimental bandgap. This observation highlights the faliure of hybrid functionals for some cases and compound-dependent nature of DFT functionals and potentials.…”
Section: Theoretical Observationssupporting
confidence: 91%
“…The GGA band gap values were determined to be 3.36 eV for Zn 3 P 2 O 8 and 2.3 eV for Zn 3 V 2 O 8 , whereas the TB-mBJ band gap values were found to be 6.17 eV for Zn 3 P 2 O 8 and 3.18 eV for Zn 3 V 2 O 8 . It is worth noting that our calculations are in alignment with earlier theoretical reports on Zn 3 V 2 O 8 , [37,38] [39] where even the GW band gap was found overestimating the experimental bandgap. This observation highlights the faliure of hybrid functionals for some cases and compound-dependent nature of DFT functionals and potentials.…”
Section: Theoretical Observationssupporting
confidence: 91%
“…Finally, various approaches to study CsCaF 3 at ambient pressure were employed in Refs. [17][18][19][20]. It also can be noticed that the spectroscopic properties of various impurities in these perovskites were studied, for example, Ni 2+ [21] and Gd 3+ [22] in RbCaF 3 , V 2+ [23] and Cr 3+ [24] in CsCaF 3 , Pr 3+ and Ce 3+ in KCaF 3 [25].…”
Section: Introductionmentioning
confidence: 97%
“…It has been found that the materials are indirect bandgap insulators and have a stable equilibrium lattice constant, elastic constants, and bulk modulus. [6][7][8] The energy band gap of uoropyrocytes is oen large, so these compounds are technologically important. 9-11 KMgF 3 and BaLiF 3 are utilized in optical lithography steppers as vacuumultraviolet materials for lenses [11][12][13] and when doped with lanthanide ions Ce and Er, KMgF 3 also shows promise as a material for radiation dosimeters and scintillation.…”
Section: Introductionmentioning
confidence: 99%